Representations of the Feminine in Nineteenth-Century English-Canadian Religious Melodrama - Jones, Heather (My University, 1993)
This study develops a theory of melodrama based on Foucaldian concepts of power/resistance relations in discourse. This theoretical framework is tested by means of an analysis of five nineteenth-century English-Canadian texts: Elizabeth Lanesford Cushing's Esther (1840), Charles Heavysege's Saul (1859), Archibald Lampman's "David and Abigail" (1882), Oliver J. Booth's Jael, The Wife of Heber the Kenite (1901), and George Arthur Hammond's The Crowning Test (1901). The central premise posed in the study's Introduction is that melodrama's protestant aesthetic of the feminine deliberately counters the secular aesthetic of tragedy. Chapter One demonstrates that this premise reveals challenges and insights concerning melodrama not previously found in the critical literature. By means of the analysis of the texts given Chapters Two, Three, and Four, the study demonstrates the interpretive strategies made possible by this re-evaluation of the genre and its gender politics. The theoretical framework developed here contributes to an understanding of melodrama both as a trans-national genre and as central feature of nineteenth-century English-Canadian culture.
Keywords: English Canadian; Melodrama